Role of Diffusion-weighted MR Imaging in the Differentiation of Benign Retroperitoneal Fibrosis from Malignant Neoplasm: Preliminary Study - VELİOĞLU, ARZU (RADIOLOGICAL SOC NORTH AMERICA, 2014)
Purpose: To evaluate diffusion-weighted imaging (DWI) features and signal intensity values at T2-weighted magnetic resonance (MR) imaging for differential diagnosis of benign retroperitoneal fibrosis (RPF) and plaque-like retroperitoneal malignant neoplasms. Materials and Methods: Institutional review board approval and informed consent were obtained for this retrospective study. Fifty-one patients with plaque-like confluent retroperitoneal soft-tissue masses were divided into three groups: group I, 25 patients with malignant RPF and retroperitoneal malignant neoplasm; group II, 16 patients with chronic RPF; and group III, 10 patients with active RPF. On T1-weighted (unenhanced and contrast material-enhanced), T2-weighted, and DWI (b = 1000 sec/mm(2)) images, apparent diffusion coefficient (ADC) values and quotients of postcontrast signal intensities between lesions and psoas muscle were evaluated. The chi(2) test was used to compare categorical values; one-way analysis of variance and Kruskal-Wallis tests were used to compare groups. Results: Overall sensitivity, specificity, and positive and negative predictive values of DWI findings were 92% (23 of 25 patients), 62% (16 of 26 patients), 70% (23 of 33 patients), and 89% (16 of 18 patients), respectively. Mean ADC values were 0.79 +/- 0.19 in group I, 1.43 +/- 0.16 in group II, and 0.91 +/- 0.14 in group III. When comparing values, differences between groups I and II (ADC values, P < .0001; DWI quotients, P < .0001; postcontrast quotients, P = .001) and groups II and III (ADC values, P < .0001; DWI quotients, P = .016; postcontrast quotients, P = .04) were significant. There was no significant difference between groups I and III or between the three groups when T2-weighted values were compared. Conclusion: ADC of chronic RPF was higher than that for active RPF or malignant RPF and retroperitoneal malignant neoplasm. DWI can contribute to differential diagnosis of chronic RPF and malignant neoplasms with RPF morphology. Lesions in the malignant group and active RPF group had similar enhancement patterns, while those in the chronic RPF group demonstrated less enhancement. Signal intensity values on T2-weighted images were not useful for differentiating these conditions.
Keywords: CT; FEATURES; PERIAORTITIS; TOMOGRAPHY